Model Pembelajaran PANORAMA Sebagai Upaya Penguatan Aktivitas, Berpikir Kritis dan Kerja Sama IPAS Kelas IV - zahratun nisa; Ahmad Suriansyah; Ratna Purwanti (CV. ITTC INDONESIA, 2025)
The implementation of Natural and Social Sciences (IPAS) subject within the context of Kurikulum Merdeka encounters several obstacles in developing 21st-century competencies. Problem identification results at SDN Pemurus Baru 2 Banjarmasin indicate minimal active student participation during the learning process, weak analytical thinking and problem-solving abilities, and ineffective teamwork and collaboration activities. This situation is further exacerbated by the limited creativity of educators in implementing innovative learning model and media variations. The purpose of this research is to optimize learning participation, critical thinking skills, and cooperative attitudes of fourth-grade students in IPAS subject with a focus on